2018
DOI: 10.1016/j.energy.2018.08.070
|View full text |Cite
|
Sign up to set email alerts
|

Cost optimal scenarios of a future highly renewable European electricity system: Exploring the influence of weather data, cost parameters and policy constraints

Abstract: Cost optimal scenarios derived from models of a highly renewable electricity system depend on the specific input data, cost assumptions and system constraints. Here this influence is studied using a techno-economic optimisation model for a networked system of 30 European countries, taking into account the capacity investment and operation of wind, solar, hydroelectricity, natural gas power generation, transmission, and different storage options. A considerable robustness of total system costs to the input weat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 37 publications
5
70
0
Order By: Relevance
“…The need for hydrogen is also reduced due to the lower economic impact of wind curtailment. The reader is referred to [46] for extended analyses on the influence of weather data, cost parameters and policy constraints on the power system optimal configuration.…”
Section: Sensitivity To Model Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for hydrogen is also reduced due to the lower economic impact of wind curtailment. The reader is referred to [46] for extended analyses on the influence of weather data, cost parameters and policy constraints on the power system optimal configuration.…”
Section: Sensitivity To Model Assumptionsmentioning
confidence: 99%
“…Fifth, only one year has been used to represent variability of renewable generation. In [46], 4 years of weather data were used to analyse the system sensitivity, and the cost of the power sector was found to be stable, although extensive sensitivity analysis to weather data such the one in [48] are desirable. Sixth, the coarse grained network used here might also impact the results.…”
Section: Limitations Of the Analysismentioning
confidence: 99%
“…Other factors that could raise the sensitivity problem are the cost assumptions, such as the ratio of capital costs between wind and solar. Schlachtberger et al [39] evaluated the influence of weather data, cost parameters, and policy constraints to the cost-optimal highly renewable European electricity system. Although the mentioned sensitivities were observed, the authors found the total system cost to be robust to different years of weather data and moderate changes in the cost assumptions.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…This constraint is set to a reduction of emissions of 95% compared to 1990 levels. Since the only fossil fuel generators in the model are open cycle gas turbines, the constraint (7) directly translates into the amount of fuel burned by these generators, and thus into the amount of power generated from this source [16], [17].…”
Section: Power System Modellingmentioning
confidence: 99%